Rancang Bangun Alat Pengontrol Suhu pada Proses Pengomposan Sampah Berbasis Mikrokontroler Atmega8 - Nugroho, Wahyuananto Agung; Prasetyo, Joko; Luthfi, Musthofa (Jurnal Rekayasa Mesin, 2011)
Compost is organic materials like leaves, straws, reeds, grasses, and even the animal faces which have experienced decomposition process by micro organism so can be used to repair the nature of soils. The aims of this research are (1) Designing Temperature Controller system by using LM35 temperature Censor with Atmega8 microcontroller, (2) Designing and constructing software using C language program to control temperature automatically, (3) Testing temperature controller device at composting machine. Research parameters include censor calibrating, microcontroller testing, and whole device testing. The research conduction got the result for temperature sensor 1, 2, 3, and 4 used LM35 censor at range 25oC – 70oC. Linear regression for censor 1: y = 0.098x + 2.059 determination coefficient score is 0,996. Linear regression for censor 2: y = 0.101x + 0.876 determination coefficient score is 0,995 Linear regression for censor 3 and 4: y = 0.098x + 2.059 with determination coefficient = 0,996. From the whole device testing, first step intake of temperature data, 30 minutes interval for 3 days: deviation score 1st day = 0.98, 2nd day = 0.906, and 3rd day = 0.937. Controlled temperature composting needs less time and produce less stink than composting without temperature control.Keywords : composting, controlling, microcontroller, temperature.